SISTEM APLIKASI KRAN OTOMATIS UNTUK PENGHEMATAN AIR BERBASIS MIKROKONTROL Atmega 16 - -, Subandi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Conventional faucet by twisting operation can be replaced with automation systems for the purpose of easy operation and to save water. Solutions to these can be solved utilizing electronic technology. With the use of sensors on the electronic switch circuit faucet and filling water in the reservoir will work automatically according to the expected circumstances. Thus the tap to remove the water and do not need to stop playing, because tap water out if a member body directed to the front of the sensor and stop the flow water if it is not directed at members of the body. While in the reservoir, water will always be awake capacity so there is no excess water runs out or when charging. In detecting the presence or absence hand directed towards utilizing sensor ultrasonic and as overall system control using AVR microcontroller atmega16. While on the test results show that there are differences in the amount of water volume released on automatic washing appliance less the regular tool so that there is efficient use of water. Based on the testing tool can be run well and as a tool in this thesis is a simulation then to apply it in real conditions necessary adjustments to take into account such things as the distance between the electrodes used in the reservois, the distance between sensor ultrasonic and distances between each faucet. This system will work automatically turn on the faucet using ultrasonic sensors as an object detector.